Early Quail Hunting Season in Tennessee: Reasons and Results - Chester A. McConnell (National Quail Symposium Proceedings, 2017)
Bobwhite quail (Colinus virginianus) wings were collected and aged from 1952 through 1970. The wing age data indicated that Tennessee's quail hunting season could begin 20 days earlier than the traditional Thanksgiving Day opening, providing a larger quail harvest. A study involving a season opening date of 5 November was conducted on Laurel Hill Wildlife Management Area resulting in an 18% increase in quail kill over previous years. Only 18% of the quail bagged on Laurel Hill were <12 weeks of age, indicating that birds were sufficiently developed to provide good sport. Based on these earlier studies, the Commission opened the statewide quail season on 6 November 1971. A total of 5,270 quail wings were collected and aged during the early season. An estimated 180,000 additional quail were harvested as a result of the earlier season. Approximately 18 to 19% of the quail were <12 weeks of age. Based on data resulting from a questionnaire, approximately 80% of the quail hunters furnished information favorable to the early season. Weather conditions during the early season were unseasonably warm, but 64% of the hunters indicated that warm weather was only a minor problem. Landowners (87%) indicated that unharvested crops were only a minor problem. Hunters (80%) indicated that young quail presented only minor problems. Sportsmen responding to the questionnaire averaged 8.1 hunting trips and bagged an average of 5.0 quail per trip in November.